Longevity in the South Carolina Alzheimer’s disease registry - Miller, Maggi C.; Mishio Bawa, Eric; Absher, John R.; Bonilha, Leonard; Ross, Lesley A.; Chai, Hye Won; Milano, Nicholas J.; Adams, Robert J. (Frontiers in Neurology, 2024)
Background South Carolina has arguably the most robust Alzheimer’s Registry in the United States. For enhanced planning in both clinical practice and research and better utilization of the Registry data, it is important to understand survival after Registry entry. To this end, we conducted exploratory analyses to examine the patterns of longevity/survival in the South Carolina Alzheimer’s Disease Registry. Methods The sample included 42,028 individuals in the South Carolina Alzheimer’s Disease Registry (SCADR). Participants were grouped into four cohorts based on their year of diagnosis. Longevity in the Registry (LIR), or the length of survival in the registry, was calculated based on the years of reported diagnosis and death. Results The median LIR varied between 24 to 36 months depending on the cohort, with 75% of individuals in the three recent cohorts surviving for at least 12 months. Across all cohorts, 25% of the participants survived at least 60 months. The median LIR of females was longer than that of males. Individuals whose race was classified as Asian, American Indian, and other than listed had longer LIR compared to White, African American, and Hispanic individuals. Median LIR was shorter for Registry cases diagnosed at an earlier age (less than 65 years). Conclusion Our data indicate that significant longevity is to be expected in the SCADR but that there is interesting variability which needs to be explored in subsequent studies. The SCADR is a rich data source prime for use in research studies and analyses.